Development of hydrogel microparticles based on sodium alginate and cellulose derivatives for controlled delivery of bovine serum albumin - Guerrero, Rodel D.; Tumolva, Terence P. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Microencapsulation is a widely used method in pharmaceutical industries to improve stability, delivery and to control the release of encapsulated core materials. Among encapsulation matrices, alginate is preferred due to its low cost, biodegradability and biocompatibility. However, for therapeutic protein drugs, the use of alginate hydrogel microencapsulating material promotes early burst release in the human gastrointestinal tract, therefore promoting low bioavailability. From this perspective, an alginate-cellulose derivative microsystem, using bovine serum albumin (BSA) as model protein, was developed using external ionotropic gelation method with calcium chloride as the crosslinking solution. Among the cellulose derivatives used were hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), and carboxymethyl cellulose (CMC). Various formulations of the different alginate/cellulose derivatives composite microparticles were prepared and results showed good morphologies and particle size and size distribution. But compared to other samples, 1:1 ratio of alginate and HEC promoted the highest encapsulation efficiency and better release behavior in simulated gastric and intestinal fluids. This study also evaluated the effects of varying the protein loading, the crosslinking solution concentration, as well as the polymer (alginate/HEC) concentration on the microsystem properties. Result presented that both the encapsulation efficiency and rate of drug release of the samples decrease when protein loading is increased; variation in the crosslinking solution concentration gives no significant effects on encapsulation efficiency but showed decrease in cumulative drug release as concentration is increased; and change in alginate/HEC concentration shows a strong quadratic relationship on both the encapsulation efficiency and rate of protein release on the microparticle system. Furthermore, to understand the behavior of drug release-rate kinetics of the microparticles and describe the transport mechanism of the protein drug in the microsystem, model independent method was used. Lastly, in order to maximize protein encapsulation efficiency, the process was optimized using Box Behnken method and resulted to the following conditions: 15 % protein loading, 2 wt. % alginate/HEC concentration, and 3 wt. % crosslinking solution concentration.
Thesis (Doctor of Philosophy in Chemical Engineering)--University of the Philippines Diliman
Keywords: Alginates; Microencapsulation; Drug delivery systems